Diabetes mellitus patients in Indonesia: management in a tertiary hospital compared to primary health care - Hikmat Permana; Raspati Cundarani Koesoemadinata; Nanny Natalia Mulyani Soetedjo; Nury Fitria Dewi; Novi Jayanti; Sofia Imaculata; Rovina Ruslami; Bachti Alisjahbana; Susan Margaret McAllister (Universa Medicina, 2022)
Background The increasing prevalence of diabetes mellitus (DM) requires that patients have greater access to care, which is yet lacking in many low- and middle-income countries and the quality of which varies between health care facilities. We compare the characteristics, complications, and risk profile of diabetes in patients receiving care in primary and tertiary level health facilities in Bandung, Indonesia. MethodsAdult DM patients were recruited from 25 community health centres (CHCs) and the outpatient clinic at one referral hospital. Key data collected and compared to national guidelines were DM history, treatment, complications, blood pressure, height, weight, and laboratory examinations on glycated haemoglobin (HbA1c), lipid profile, and creatinine. Data analysis was by chi-square test. ResultsOf the 809 DM patients (median age 59 years, 63% female, 98% type 2 DM), 318 (39%) were from CHCs and 491 (61%) from the hospital. Overall median HbA1c was 8.3%, with no difference between CHC and hospital patients. Only 32% of patients with HbA1c ≥10% were on insulin (CHCs 5.9%, hospital 42.9%), and only 18% of those on insulin had glycaemic control. Hypertension was common (CHCs 62%, hospital 51%, p<0.001), and only 44% of CHC and 34% of hospital patients received antihypertensive therapy. Among those with macrovascular complications, only 32% (CHCs) and 26% (hospital) were receiving aspirin. The numbers reaching the treatment targets were low for those on antihypertensives and lipid-lowering medications (80/251 and 11/105, respectively). ConclusionGlycaemic control and management of complications of DM patients at both health care levels need considerable improvement.